The Broken Home Narrative on TikTok: An Analysis of Content Hashtag #BrokenHome - Efendi, Moh Alvian; Nasvian, Moch Fuad (KONTEKSTUAL : Jurnal Ilmu Komunikasi, 2025)
TikTok is a popular global social media platform, yet limited research has examined how it is used to express emotional experiences related to family trauma such as broken homes. The hashtag #brokenhome has become a space for sharing personal stories and emotions about family disruption, but the content patterns and user engagement in these videos remain underexplored. This study aims to analyze the dominant emotional themes in TikTok videos tagged #brokenhome, investigating how creators share their experiences, offer advice, and evoke emotional responses. A summative content analysis was conducted on the top 100 most-viewed #brokenhome TikTok videos (June 15, 2020 to January 25, 2025). Results show that personal narratives and emotional expressions (especially sadness) were the most common content themes, followed by advice/information and social support. Notably, no videos were promotional and only one was misleading. Personal narrative and emotionally expressive videos garnered the highest user engagement, while videos offering social support also saw significant interaction. These findings highlight TikTok’s role as a platform for emotional expression, identity formation, and communal healing, with implications for understanding social media’s role in emotional support and mental health.